Control feedback and cellular responses - Doyle III, Francis J. (Henry Stewart Talks, 2014)
Early origins of systems biology, Basic tools from dynamics and feedback control -Robustness in biology, Biological versions of control loops, Analysis tools to interrogate biophysical circuits, Case study: Circadian Rhythm, Importance of performance specification, Phase response curve (PRC), Stochastic sensitivity analysis, Bootstrap methods, The advantage of multiple models, Generating hypotheses, Systems biomedicine and the pharmaceutical industry perspective